Clinical and Head Ultrasound Findings in Neonates after Administration of High Dose of Vitamin A - R M Nurrachim; Ali Usman; Sjarif Hidajat; Dedi Subardja; Tina Agoestina; Jean Humphrey; George A. Taylor (Paediatrica Indonesiana, 1994)
Vitamin A deficiency is a major cause of blindness and severe morbidity and mortality in young children. Supplementation of vitamin A in the community might reduce child mortality rates. The safety of high dose of vitamin A administered to neonates is not clear. We randomized 2058 neonates to receive either a single dose of 50 000 IU oral vitamin A (n=l031) or placebo (n=l027). Bulging fontanel and head circumference were assessed before and throughout 48 hours following dosing. Cranial ultrasound examination was carried out in 972 infants before and 24 hours after dosing to rule out intracranial hemorrhage and determine resistive index (Rl) of the anterior cerebral artery. Slight bulging fontanel occurred in 2. 7% and 4.4% of the infants at 24 hours. Moderate bulging fontanel was seen in 0.1% of study group, no severe bulging was observed. At 48 hours slight bulging fontanel was observed in 2.4% of control group and 4.5% in study group. No intracranial hemorrhage was found. Mean RI values were normal in both groups at baseline or 24 hours. Bulging fontanel was not associated with increased signs or symptom, or with increase in RI. Single oral dose of 50 000 vitamin A may cause a small increase in intracranial volume in a small proportion of infants, without increase in intracranial pressure.